Volume 6: Structures and Dynamics, Parts a and B 2010
DOI: 10.1115/gt2010-22058
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Experimental and CFD-Based Theoretical Methods for Studying Rotordynamic Characteristics of Labyrinth Gas Seals

Abstract: This paper presents an analysis of the experimental and theoretical methods used to study rotordynamic characteristics of short staggered labyrinth gas seal. Two experimental identification procedures referred to as static and dynamic methods are presented. The static method allows determining direct and cross-coupled stiffness coefficients of the seal by integrating measured circumferential pressure distribution in cavities at various shaft eccentric positions. In the dynamic method, identification of stiffne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…along the seal (see Refs. [1,8]). Seal regions with high eccentricity ratio Ô = els (where s is the cavity height) dominate the formation of the radial force, i.e., direct stiffness.…”
Section: Grid Independence Studymentioning
confidence: 96%
See 4 more Smart Citations
“…along the seal (see Refs. [1,8]). Seal regions with high eccentricity ratio Ô = els (where s is the cavity height) dominate the formation of the radial force, i.e., direct stiffness.…”
Section: Grid Independence Studymentioning
confidence: 96%
“…Secondly, experimental and theoretical analysis presented in Ref. [1] showed that the difference in global and local cross-coupled stiffness coefficients was not significant for the SSS seal with the radial clearance of 0.27 mm, only the direct stiffness demonstrated large discrepancy between two methods. The values of local and global damping coefficients were also in good agreement.…”
Section: Local Rotordynamic Coefficientsmentioning
confidence: 97%
See 3 more Smart Citations